Iwo Jima legacy of valor - Ross, Bill D. (Vanguard Pr., 1985)
Chronicles the United States assault against the Japanese forces on Iwo Jima in 1945.
Keywords: Iwo Jima, Battle of, Japan, 1945; Schlacht auf Iwojima